Continuous aridification since the mid‐Holocene as the main cause of C3/C4 dynamics in the grasslands of northeastern China. (22nd April 2020) - Li, Nannan; Xie, Manman; Sack, Dorothy; Dubois, Nathalie; Yang, Xiuyun; Gao, Guizai; Li, Dehui; Liu, Lidan; Liu, Hongyan; Leng, Chengcheng; Wang, Jiangyong; Liu, Baojian; et al.
Abstract: Ecological responses to past climate change as determined from palaeorecords offer insights into responses that may accompany future climate change. In arid and semi‐arid lands, the interactions between regional vegetation and climate change are not yet well understood, partly due to a lack of suitable palaeovegetation proxies that can provide accurate and continuous tracers for past vegetation dynamics. To gain a better understanding of long‐term vegetation dynamics, this study employs a multiproxy approach applied to sand‐palaeosol sediments of northeastern China's Songnen grasslands. Phytolith analyses and data on the stable carbon isotope composition ( δ 13 C) of organic matter are used to reconstruct palaeovegetation composition, namely, the changing abundance of C3 and C4 species, whereas a geochemical weathering index (Fed/Fet ratios) tracks past East Asian summer monsoon (EASM) intensity. The phytolith assemblages and indices and δ 13 C of the soil indicate that C4 species' abundance has been increasing in the Songnen grasslands since the mid‐Holocene, although C3 vegetation is still dominant. Statistically significant negative correlations between the δ 13 C data and Fet/Fed ratios suggest that continuous weakening of the EASM since the mid‐Holocene may be responsible for the 13 C‐enrichment of the sediments in the Songnen grasslands. Field vegetation surveys, modern topsoil phytoliths and δ 13 C calibration data indicate that the expansion of C4 species since the mid‐Holocene is mainly due to their ability to cope with aridity when growing season temperature is not undergoing a significant decrease. Future precipitation decreases in arid and semi‐arid lands should make C4 species more competitive in the grasslands of northeastern China. Highlights A continuous grassland landscape history is reconstructed from a sand‐palaeosol sequence via phytolith analysis. Multiple independent approaches were used to reconstruct past EASM intensity and palaeovegetation patterns. Phytolith and δ 13 C analyses indicate an increase in C4 species since the mid‐Holocene. Aridification drives the increase in C4 species within the grassland ecosystem.